Rapid characterisation of Mars' mantle reservoirs by in situ laser ablation 87Sr/86Sr analysis of shocked feldspar (maskelynite) - Burgin, Daniel L.; Scott, James M.; le Roux, Petrus J.; Howarth, Geoffrey; Palmer, Marshall C.; Czertowicz, Thomas A.; Negrini, Marianne; Reid, Malcolm R.; Stirling, Claudine H. (Geochimica et cosmochimica acta, 2023)
The 87Sr/86Sr isotopic properties of martian meteorites, measured by isolation and purification of Rb and Sr fractions, have long been used to partially characterise Mars' mantle. However, this method is time-consuming, destructive, and subject to incorporation of terrestrial contamination due to precipitation of phases in fractures and/or grain boundaries prior to meteorite collection. In this study, we test the effectiveness of in situ acquisition of 87Sr/86Sr by laser ablation in maskelynite - a typically low Rb/Sr (<0.1) feldspar-composition glass formed during high-P shock metamorphism – as a method of rapid characterisation of Mars' mantle Sr isotope ratios. Element concentration maps and the results of unwashed and gently surface-leached bulk rock analyses indicate that terrestrial Sr has infiltrated the studied meteorites and affected bulk rock trace element budgets. However, maskelynite trace element concentrations are largely unaffected and their martian igneous Rb/Sr is preserved. In situ87Sr/86Sr analyses of maskelynite, checked against a newly developed Sr feldspar reference material (KAN, presented here and available on demand), accurately and precisely distinguish different shergottite mantle reservoirs. The measurements reproduce published data, have uncertainties on the 4th to 5th decimal place, and yield statistically indistinguishable results in analytical sessions separated by long periods of time. The data from 11 enriched shergottites reveal there to be subtle Sr isotope variation within the enriched shergottite mantle reservoir, or that there was crustal assimilation of radiogenic components into the shergottites, or that the shergottite liquids were extracted over a time period during which the mantle reservoir 87Sr/86Sr evolved. The limited published age range of the enriched shergottites, coupled with the absence of a correlation between in situ87Sr/86Sr and REE, Sr or Pb concentration in maskelynite, suggests that the isotope range is best explained by small variations in the enriched mantle reservoir. Given the presence of maskelynite (or plagioclase) in many meteorites, the in situ method will be useful when there are only very small volumes of material available and/or where terrestrial contamination is suspected.